Critique and Analysis of Views in the Verse «لَتَرْکَبُنَّ طَبَقًا عَنْ طَبَقٍ» (That Ye Shall Journey on from Plane to Plane) and Its Understanding Based on Polysemy Theory - Leila Alikhani; Ahmad Zare Zardini; Muhammad Hossein Boroumand; Amir Joudavi (آموزه‌های قرآنی, 2021)
The nineteenth verse of Sūrah al-Inshiqāq, in which the commentators have expressed different views and sometimes called it concise, has several meanings. The meaning of polysemy in the verse is not in the sense of ambiguity of meaning that occurs without the intention of the speaker in the word; Rather, it indicates the power and wisdom of God in choosing words and combinations that express several meanings at the same time and all meanings are also His purpose. The present study, which is written with a critical-analytical method, first explains the views of the commentators and after a brief review of the views, examines the polysemy hypothesis in the verse. The contexts and factors affecting the occurrence of this issue in the verse under discussion are: polysemy of the morpheme and words of the verse, multiplicity of readings, syntactic structure of the sentence and the linguistic context of the surah or method. The aspects of the meanings that can be enumerated for the verse are: 1- following the predecessors and the occurrence of divine precedents (practice, approved) among the audience of the Qur'an, 2- Generation transformation, 3- Entering the resurrection desert, 4- Entering among the previous Ummah (followers) in hell, 5- Human ascent to heaven, 6- The Ascension of Prophet Muhammad (PBUH). Due to the non-conflict between the mentioned meanings with each other, with the totality of the text and the axiomatic (certain) religious teachings, all of them can be accepted as various meanings of the verse and the possible meaning of God Almighty.